Caawiye app
Welcome to Caawiye app, a platform to connect with the social world
Don't have an account?Sign Up
Caawiye app
Welcome to Caawiye app, a platform to connect with the social world
Already have an account?Login
Stay connected
M | T | W | T | F | S | S |
---|---|---|---|---|---|---|
1 | 2 | 3 | 4 | 5 | ||
6 | 7 | 8 | 9 | 10 | 11 | 12 |
13 | 14 | 15 | 16 | 17 | 18 | 19 |
20 | 21 | 22 | 23 | 24 | 25 | 26 |
27 | 28 | 29 | 30 | 31 |
1 Answers
caawiye Admin
We can start by using the trigonometric identity:
sin(2x) = 2sin(x)cos(x)
We can substitute this identity into the expression:
(tan(x) – 1)(sin(2x) – 2cos²(x))
= (tan(x) – 1)(2sin(x)cos(x) – 2cos²(x)) (substituting sin(2x) with 2sin(x)cos(x))
= -2cos(x)(tan(x) – 1)(cos(x) – sin(x)) (factoring out a -2cos(x) from the second term)
= -2cos(x)(sin(x) – cos(x))(tan(x) – 1)(-1) (multiplying the second term by -1 and rearranging)
= 2cos(x)(cos(x) – sin(x))(1 – tan(x))
= 2cos(x)(cos(x) – sin(x))(1 – sin(x)/cos(x)) (substituting tan(x) with sin(x)/cos(x))
= 2(cos(x) – sin(x))(cos(x)/cos(x) – sin(x)/cos(x))
= 2(cos(x) – sin(x))(1 – sin(x)cos(x)/(cos(x))^2)
= 2(cos(x) – sin(x))(1 – sin(x)cos(x))
= 2(cos(x) – sin(x) + sin(x)cos(x) – sin(x)²cos(x))
= 2(1 – sin(x)cos(x) – 2sin(x)cos(x))
= 2(1 – 3sin(x)cos(x))
= 2(1 – 2sin(x)cos(x) – sin(x)cos(x))
= 2(1 – 2sin(x)cos(x)) (since sin(x)cos(x) = 1/2 sin(2x))
Therefore, (tan(x) – 1)(sin(2x) – 2cos²(x)) = 2(1 – 2sin(x)cos(x)) as required.